Analisis Strategi Pemasaran Produk Kowi dan Hot Plate Menggunakan Metode SWOT dan Quantitative Strategi Planing Matrix (QSPM) - Suhandri; Nugroho, Andung Jati (As-Syirkah: Islamic Economic & Financial Journal, 2025)
The globalization of economic development has heightened industrial competition, impacting small and medium enterprises (SMEs) in Indonesia. CV Andhy Karya, a metal casting company in Klaten, Central Java, specializes in producing aluminum melting pots (Kowi) and hot plates. Despite utilizing modern technology, the company experienced a decline in sales from October 2023 to March 2024 due to fierce competition and inefficient marketing and distribution strategies. This study aims to analyze the marketing strategy of CV Andhy Karya using a quantitative approach with SWOT and QSPM methods. Internal and external factors of the company are evaluated through the IFE and EFE matrices. The results show that CV Andhy Karya has improved its marketing by focusing on product quality, accelerating raw material delivery, and utilizing the latest technology. The company also conducts regular training to enhance employee performance. The internal factor analysis reveals strengths in team cooperation, while weaknesses are found in the distribution system. Opportunities arise from collaboration with government institutions, while threats come from competition. Based on the QSPM analysis, the company chooses strategies such as adopting the latest technology, expanding marketing efforts, and focusing on the industrial market.